Elaboración de una guía didáctica de lectura crítica en el área de lengua y literatura para el 7mo. Año de educación básica de la escuela 12 de Octubre comunidad La Florida del cantón Ponce Enríquez periodo 2012 - 2013. - Cruz Castillo, Karen Julissa (2015)
In addressing the issue of critical analysis reader, we start with one of the problems that most strongly affects teachers and certainly reading is the key to learning the different areas of study pillar , so it is important to consider the process to help expand reading skills both in teaching and in the deponent .